Parameter Optimization for Soil Tillage and Weed Control Using Combined Response Surface Method and Modified Differential Evolution Method - Srichok, Thanatkij; Chomchalao, Chaiya; Pitakaso, Rapeepan; Khonjun, Surajet (Princess of Naradhiwas University Journal, 2021)
This study presents a method to find the optimal operating parameters of a tractor disk plow that maximizes the width of soil tillage and weed control. The method used to find the parameters comprised of 4 steps including (1) identifying the number of interesting parameters and their levels, (2) determining the appropriate parameters using the RSM method, (3) finding the optimal parameters using RSM-MDE and (4) checking results of the third procedure. The computational results showed that the most effective optimal parameters were improved by the RSM-MDE method with disk angle of 45 degrees, a tilt angle of 19.34 degrees, and speed of 3 km./hr. The width of soil tillage and weed control was 139.20 cm. which was wider than of the RSM method (137.44 cm). This result indicated that the RSM-MDE method can provide better solution by 1.28% than the original RSM.